2014
DOI: 10.1590/s1415-43662014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética na busca de eficiência à produção de sementes e biomassa de capim Sudão

Abstract: R E S U M OObjetivou-se, com o estudo, conhecer a variabilidade genética de caracteres ligados à inflorescência em populações de capim Sudão e a contribuição dessas variáveis na definição do caráter mais efetivo na seleção para a produtividade de sementes. Além disto, fornecer subsídios em indicar que a pressão de seleção sobre os componentes da panícula visando aos incrementos na produção de sementes, não compromete os caracteres de interesse forrageiro. Os experimentos foram realizados nos anos de 2009 e 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…Freitas et al (2012) state that the use of legumes for straw production is a favorable management; it increases the content and availability of nitrogen fertilizer in the soil for culture succession. Silva et al (2014) found that the panicle mass of Sudan grass is the component that expresses highest variability in the panicle characters. In oat (A. sativa), Hartwig et al (2006) concluded that the panicle mass increment is based on the increased number of grain per panicle, with little effect of the grain mass of panicle.…”
Section: Resultsmentioning
confidence: 96%
“…Freitas et al (2012) state that the use of legumes for straw production is a favorable management; it increases the content and availability of nitrogen fertilizer in the soil for culture succession. Silva et al (2014) found that the panicle mass of Sudan grass is the component that expresses highest variability in the panicle characters. In oat (A. sativa), Hartwig et al (2006) concluded that the panicle mass increment is based on the increased number of grain per panicle, with little effect of the grain mass of panicle.…”
Section: Resultsmentioning
confidence: 96%
“…The relative contribution analysis allows knowing the traits that contribute most to the total variability [2]. Research [24] reports that in Sudangrass, there is the possibility identification of plants more efficient to use environmental stimuli by panicle weight and number grain per panicle. [25] studying oats, also found in the panicle weight the greatest contribution in the identification of plants with higher grain yield variability observed in inflorescence components.…”
Section: Resultsmentioning
confidence: 99%
“…O potencial de uso dos marcadores moleculares no melhoramento de plantas é bastante amplo, destacando-se a identificação e discriminação de genótipos, quantificação da variabilidade genética ao nível de sequencias de nucleotídeos no DNA (BERTAN et al, 2009), quantificação da variabilidade genética, identificação de origem parental, determinação de formas de reprodução e monitoramento de cruzamentos (SILVA et al, 2014). Algumas amostras não apresentaram bandas(Figura 1 e 2) , como não se observa a formação de rastros de fragmentos na linha do gel, pode-se inferir que não ocorreu degradação das amostras utilizadas; essa situação pode ser explicada pela interferência em função do alto nível de impureza das amostras obtidas por este método ou mesmo pela perca do pellet no processo de lavagem com álcool (ROBYT & WHITE, 1990;BARBOSA, 1998;NÓBREGA et al, 1999).…”
Section: Introductionunclassified